2001
DOI: 10.1080/0955300010000809
|View full text |Cite
|
Sign up to set email alerts
|

Physical heights of children with prolonged low dose-rate γ-radiation exposure in radiocontaminated buildings

Abstract: Prolonged low dose-rate y-radiation exposure was associated with adverse effects on the physical heights of growing boys, but were less apparent in the exposed girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…More than 20 years since the disclosure of this event, numerous scholars have reported adverse radiation-related physical effects caused by Taiwan RCB (Chang WP et al 1997b, 1999a, 1999b, 1999c, Chang TC et al 2001, Wang et al 2001, Hwang et al 2006, Lin et al 2010; however, few studies have evaluated how the low-dose rate irradiation affected mental health in this unique cohort. A previous study indicated that the exposed population exhibited significantly lower health-related quality of life (HRQoL) scores in the physical, psychological, and social relationship domains than did unexposed members of the general population in the same city (Yen et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…More than 20 years since the disclosure of this event, numerous scholars have reported adverse radiation-related physical effects caused by Taiwan RCB (Chang WP et al 1997b, 1999a, 1999b, 1999c, Chang TC et al 2001, Wang et al 2001, Hwang et al 2006, Lin et al 2010; however, few studies have evaluated how the low-dose rate irradiation affected mental health in this unique cohort. A previous study indicated that the exposed population exhibited significantly lower health-related quality of life (HRQoL) scores in the physical, psychological, and social relationship domains than did unexposed members of the general population in the same city (Yen et al 2011).…”
Section: Introductionmentioning
confidence: 97%